Mucositis induced by oncologic treatments: a literature review - Silva, Marlene (2014)
Mucositis is a frequent and debilitating complication of cancer treatment. Mucositis may result from systemic cytotoxic effects of chemotherapy or radiation local effects on the oral mucosa and gastrointestinal tract. These methods of cancer treatment, in addition to destroy neoplastic cells that proliferate rapidly, they also destroy the epithelial cells of oral mucosa and gastrointestinal tract and can induce a complex cascade of biological events that contribute to ulceration of the mucosa. The severe mucositis has a significantly negative impact on well-being, quality of life and activities of daily life of the patient. Can also compromise the ability to tolerate the treatment and resulting in reduced doses or postponements. Mucositis may also involve a significant economic burden due to prolonged hospitalization and the use, if necessary, of analgesics, antibiotics, and parenteral nutrition, which represents a substantial increase in treatment costs. Recently, new guidelines have been published with the aim of directing the use of drugs and uniformize measures which contribute to the resolution of mucositis. The knowledge that nurses have in the medical sciences and humanities allow not only acting, but also understand, evaluate and investigate the consequences of their interventions and sensing and monitoring how the patient experiences his disease.